LEADERSHIP, CONTRIBUTION, LANGUAGE AND SHARED CONTENT AS METRICS IN MALAYSIAN MILLENNIALS’ DECISION MAKING - May Amy, Yeo Chu; Carter, Steve; Shuo, Khor Zhan (JBFEM, 2019)
Millennials have purchasing power second only to ‘baby boomers’. This generation grew up in a time of immense and fast-paced technological change. The study aims to investigate how this particular group of consumers made the decision based on their influencers, share content and common language in a virtually connected environment. A positivist paradigm to amass data from different business undergraduates who are familiar with the various social media and online purchases were used. Results revealed positive correlations between the constructs in and also indicated that ‘factors in communicating’, ‘Influencers recommendations’, ‘opinion leaders advice’, and ‘agreements with reference partner’ were statistically significant, making a unique contribution of prediction to the decision-making process. The limitations apply to a country-specific context, small sample size and a specific type of respondent. Studies in other contexts and with different respondents may yield different results. Whilst the study has confirmed and reinforced the importance of social media as a potent force in communication to and within Millennial groups, the study has highlighted that ‘collective intelligence’ in the purchase decision-making process has emerged as a result of the coalescing of social media with other complex individual factors like methods of advice and agreement with opinion leaders.